Design and test of centrifugal disc type sowing device for unmanned helicopter - Song, Cancan; Zhou, Zhiyan; Luo, Xiwen; Lan, Yubin; He, Xingang; Ming, Rui; Li, Keliang; Hassan, Shahbaz Gul (International Journal of Agricultural and Biological Engineering, 2018)
In China, it is difficult for manned aircraft to sow seeds in small and scattered plots, especially in areas including hills, swamps, telegraph poles, windbreaks, and residential areas; in such terrain, the sowing machinery cannot function properly. However, unmanned helicopters (UHs) are flexible enough to control and adapt to the complex environments that are not easily accessible by terrain sowing machinery and large agricultural aircraft, which have been widely used in agriculture. In this study, a centrifugal disc-type sowing device for an unmanned helicopter (CDTSDUH) was designed. The factors influencing the seed velocity when the seeds move away from the disc were explored by analyzing the forces of the seed acting on the sowing disc and the wind field of the UHs. The influential factors include the distance from the falling mouth to the center of the disc, the offset angle of the falling mouth, and the rotation speed of the disc. An orthogonal test was designed with the sowing width and the curvature of the sowing area as the indexes. The test results showed that the three factors mentioned above had a greater impact on the sowing width than the curvature of the seeding area. Moreover, the superior parameters of the disc were determined. It was also suggested that the above factor levels had little effect on the offset width of sowing. The results of the test conducted for studying the sowing uniformity of the CDTSDUH indicated that the maximum and minimum difference values among the number of particles of the sampling points in the forward direction was 11 and 8, and the coefficient of variation of the number of particles in each row was more than 20%, indicating less uniformity was achieved when sowing in the lateral (perpendicular to the forward direction) direction, as compared to that in the forward direction. This study determined the ideal values for the radius of particles position, the offsetting angle, and the disc speed of the sowing machinery designed. Furthermore, considering that there are so many factors that influence the manner in which a UH functions, more analysis results and test data of influencing factors need to be acquired by experiments. The uniformity of sowing needs to be further improved. The results provided some theoretical and experimental references for the technology research on the centrifugal disc-type sowing device for UHs.Keywords: sowing, unmanned helicopter, aircraft sowing, centrifugal disc, uniformity, sowing discDOI: 10.25165/j.ijabe.20181102.3757Citation: Song C C, Zhou Z Y, Luo X W, Lan Y B, He X G, Ming R, et al. Design and test of centrifugal disc type sowing device for unmanned helicopter. Int J Agric & Biol Eng, 2018; 11(2): 55–61.